Extranodal natural killer/T cell lymphoma nasal type simulating osteoradionecrosis with metachronic B lymphoma in the pelvis: Case report - Frida S. Colín-Guadarrama; Violeta E. Flores-Solano; Argelia Berenice-Rodríguez; Víctor H. Toral-Rizo (Indian Journal of Pathology and Microbiology)
Extranodal Natural Killer/T Cell Lymphoma Nasal Type (EN-NK/T-CL-NT) is a non-Hodgkin extranodal lymphoma of unfavorable prognosis due to its aggressive nature. This neoplasm mainly affects the paranasal sinuses, nasopharynx, oropharynx, oral cavity, palate, and rarely intestinal, gastric and skin regions. 50-year-old female with a history of lymphoma in nasal and pelvic region. At four years of tumors-free, has facial asymmetry, accompanied by sub-palpebral, nasal and lip edema. Intraoral examination revealed a large ulceration suggestive of osteoradionecrosis. Gum biopsy shows Extranodal NK/T Cell Lymphoma Nasal Type (EN-NK/T-CL-NT). In this case we highlight the characteristics of EN-NK/T-CL-NT with a presentation of osteoradionecrosis-like. Unfortunately, the nature of this tumor led to the patient’s death. Clinical follow-up of patients with cancer is imperative to mend and/or decrease treatment complications, as well as to identify second primary tumors or the spread of the underlying disease.